Taḥqīq Mafhūm al-Istiṭā‘ah al-Ṣiḥḥiyyah li al-Ḥujjāj al-Ṭābūrīn fī Indūnīsiyā al-Mu‘āṣirah - Suhaili Sufyan, Muhammad; Abu Bakar, Ali; Mubarrak, Husni; Munir, Badrul; Yunus, Saifullah (Al-Zahra: Journal for Islamic and Arabic Studies, 2024)
Hajj is a pillar of Islam, obligatory for every Muslim who is financially and physically capable. This research focuses on the health condition as a key requirement for performing Hajj in Indonesia, particularly for pilgrims in long queues. Ensuring health and safety before, during, and after Hajj has become a critical aspect, mandated by Islamic law and Indonesian regulations. The condition of health and the ability to provide food and equipment, constitutes a fundamental part of the "ability" (istita'ah) required for Hajj and Umrah. This research presents some important questions about the concept of ability in Islamic jurisprudence and Indonesian law, to what extent which the meaning of ability can be applied to reality due to the large number of pilgrims queuing up for many years. This research used library studies by quoting opinions and ideas from major jurisprudential books and contemporary research as well as Indonesian law concerned with this issue. This research concludes that it is possible to reconcile Islamic jurisprudence in obligating the condition of ability for anyone who wants to perform the Hajj obligation, especially for the queues pilgrims that could not fulfill this kind of requirement, where someone can act on his behalf, as happened during the era of the prophet Muhammad PBUH.